Przeszkody małżeńskie w świetle Kodeksu Prawa Kanonicznego oraz Kodeksu rodzinnego i opiekuńczego - Maj, Zuzanna (Ius Matrimoniale, 2017)
There is no doubt that many marital impediments indicated in Code of Canon Law have not been regulated in The Family and Guardianship Code, because they result from Divine Law and from the nature of the Catholic Church. However, a part of the marital prohibitions is the same in both of these legal systems. These are most often impediments arising from natural law, to which every human is subject, regardless of national or religious affiliation. The range of marital impediments is significantly broader in Canon Law than in secular law. However, five impediments are identical in both law orders: the impediment of age, bond of marriage, consanguinity, affinity and legal consanguinity. The secular legislature implemented two marital impediments, which have not been regulated in church marital law in matters of marital impediment, but which relate to contractual defects. They are: total deprivation of liberty and the impediment of mental disorder or mental underdevelopment. Impediments existing only in canon law (impotence, difference of religion, ordination, vow, abduction, misdemeanour and public honesty) were implemented on the grounds of particular concern of the Church about marriage and the family. Obviously, due to the different nature and aim of national law, the implication of them to Polish law was not possible.